Pengimplementasian Nilai-Nilai Pancasila dan Pengembangan Potensi Desa Melalui Kesenian Tradisional Lewat Peran Pemuda di Desa Gandulan - M. Riski Amin Muminin; Senie Ariza Pranadia Sasti (Jurnal Bina Desa, 2026)
Temanggung is an area famous forits traditional arts which are part of the culture passed down from generation to generation, namelyt heart of Kuda Lumping or Jaran Kepang. Gandulan Village, which is dividedinto 4 hamlets, has a variety and characteristic sof traditional  art, namely jaran kepang. Art performances, especially jaran kepang art, are alwaysbasedon Pancasila valuesin carryingout jaran kepang artperformances. The aim of implementingthis service program is to mobilize village communities throught hero leofyouth in implementing Pancasila valuesby optimizing village potential through the role of youth. Where in this activity, KKN students together with the community, especiallyyouth, together educate each other in implementing the values of Pancasila,including exploring the potential of the village with part of the unique characteristicsth at exist in thevillage. The methodused in this research is direct observation and carrying out activities to implement Pancasila values in various activities. The results of this research are that art whichis a tradition in Gandulan villageisabletosupporttheimplementationof Pancasila valuesand develop village potential through art witht herole of village youth.